Physical fitness levels of junior high school students in different regions: Highlands, lowlands, and islands. - Apriyano, Berto (Editura Universitatii din Pitesti, 2023)
Physical Education is an integral part of the national education program, aiming to develop aspects of physical fitness and aspects of self-skills through the provision of learning experiences that use selected physical and carried out systematically. One of the goals of physical education is to improve physical fitness. This study aims to find out why the low level of physical fitness of students, whether there is an influence with the geographical location of an area, so the purpose of this study was to determine the difference in the level of physical fitness possessed by highland, lowland and island students with diverse geographical conditions in Indonesia. The highlands were in Kerinci district, Jambi, the lowlands were in Padang, West Sumatra, while the islands were in Meranti Islands district, Riau. These three regions were represented by 2-3 schools each, which were both located in city and district centers, but differ in terms of geographical categories. This design had a quantitative descriptive research type using comparative analysis. The instrument used was the existing and patented TKJI for ages 13-15 years. The sample used was the students grade VII of Junior High School. The data obtained were then analyzed by using an independent sample t-test with a prerequisite test of normality test and homogeneity test. These findings show that the average value for the highland region was 13.83; lowland areas was 13.20; and islands was 13.26. Meanwhile, based on the test results using ANOVA, the highlands have a better score. Therefore, it can be concluded that the area that has a better level of physical fitness among the three areas is the highlands area (Kerinci Regency, Jambi).